2016
DOI: 10.3389/fncel.2016.00253
|View full text |Cite
|
Sign up to set email alerts
|

ROCK1 Is Associated with Alzheimer’s Disease-Specific Plaques, as well as Enhances Autophagosome Formation But not Autophagic Aβ Clearance

Abstract: Alzheimer’s disease (AD) is the most prevalent form of late-life dementia in the population, characterized by amyloid plaque formation and increased tau deposition, which is modulated by Rho-associated coiled-coil kinase 1 (ROCK1). In this study, we further analyze whether ROCK1 regulates the metabolism of amyloid precursor protein (APP). We show that ROCK1 is colocalized with mature amyloid-β (Aβ) plaques in patients with AD, in that ROCK1 enhances the amyloidogenic pathway, and that ROCK1 mediated autophagy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The in situ cell death detection kit (FITC) (Chemicon, Temecula, CA, USA) was used to detect apoptosis in the tissue following the manufacturer's instructionsas described previously [21]. Briefly, the sections were dewaxed and rehydrated by heating the slides at 60 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The in situ cell death detection kit (FITC) (Chemicon, Temecula, CA, USA) was used to detect apoptosis in the tissue following the manufacturer's instructionsas described previously [21]. Briefly, the sections were dewaxed and rehydrated by heating the slides at 60 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, in brains of AD patients, ROCK1 immunoreactivity co‐localizes with the cores of mature Aβ plaques (Hu et al . ). Collectively these findings implicate a closely linked relationship between ROCKs and Aβ deposition/clearance.…”
Section: Role Of Rocks: Parenchymal Pathologies In Admentioning
confidence: 97%
“…Inhibition of both ROCK isoforms by fasudil achieved similar results in the APP/PS1 mouse model of AD (Yu et al 2016). In addition to Ab and APP processing, ROCK1 has been proposed as an initiator of Ab autophagy; in vitro over-expression of ROCK1 promotes internalization of Ab and increased formation of autophagosomes (Hu et al 2016). Additionally, in brains of AD patients, ROCK1 immunoreactivity co-localizes with the cores of mature Ab plaques (Hu et al 2016).…”
Section: Role Of Rocks: Parenchymal Pathologies In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our results (Figs. 3B and 3C) showed that the diabetic pathophysiological factors could upregulate ROCK1 and 14-3-3σ which are associated with neurodegeneration [32, 33]. Thus it would be interesting to investigate whether ROCK1 or 14-3-3σ is a link between type 2 diabetes and Alzheimer's disease which shows an increased risk in type 2 diabetes [34].…”
Section: Discussionmentioning
confidence: 99%